Validation of the accuracy of handheld echocardiography for diagnosis of congenital heart disease - Sulafa Ali; Tajudeen Bushari (Annals of Pediatric Cardiology, 2018)
Background: Handheld echocardiography (HHE) has been increasingly used for rheumatic heart disease screening and in adult emergency room settings. Aims: This study aimed to validate the accuracy of HHE in the diagnosis of congenital heart disease (CHD). Settings and Design Methodology: This is a prospective study carried out at three pediatric cardiology outpatient clinics in Khartoum, Sudan. All patients with suspected CHD were evaluated by clinical examination followed by HHE, performed using a modified segmental approach. Then, a complete study was performed using a standard echocardiography machine. The results were then compared using appropriate statistical tools. Results: A total of eighty cases were included with the following diagnoses either in isolation or combination: ventricular septal defect (n = 23), atrial septal defect (n = 10), pulmonary stenosis (n = 7), tetralogy of Fallot (n = 7), patent ductus arteriosus (n = 6), atrioventricular septal defect (n = 6), transposition of the great arteries (n = 6), and other diagnoses (n = 15). Agreement between HHE and SE was excellent both for visualizing heart segments (κ =77%–100% with a mean of 92.9%) and for diagnosis of CHD (κ =66%–100% with a mean of 91.7%). The sensitivity of HHE was 69.2%–100% (mean = 90.2%) and specificity was 98.5%–100% (mean = 99.3%). Conclusion: This study supports extending the utility of HHE in children for screening of CHD in addition to its current role in rheumatic heart disease screening.